Renal secondary hyperparathyroidism in a canine: case report (Research, Society and Development, 2023)
The kidneys are organs responsible for maintaining homeostasis in the body, both in humans and animals. The loss of its function promotes the retention of solutes that should be excreted and the non-reabsorption of important compounds for the body, causing toxicity and deficiencies. When kidney disease is advanced, one of the consequences is secondary hyperparathyroidism, which is characterized by the continuous increase in parathyroid hormone secretion, a physiological response due to the decrease in ionized calcium. The symptomatology depends on the degree of evolution of the disease, and osteodystrophy is frequently described in cases with involvement of the parathyroid glands. Changes such as normocalcemia or hypercalcemia associated with hyperphosphatemia and tests consistent with chronic kidney disease confirm the suspicion. The prognosis for patients with this aggravation is usually unfavorable. Therefore, the aim of this article is to describe a case of a canine, Shih tzu, where through clinical, laboratory and imaging examinations it was possible to obtain diagnostic secondary renal hyperparthyroidism.